1997
DOI: 10.1029/97ja01150
|View full text |Cite
|
Sign up to set email alerts
|

Monoenergetic ion drop‐off in the inner magnetosphere

Abstract: Abstract. A monoenergetic drop-off of ions around 10 keY, which we term as "ion drop-off band" (IDB) in this paper, has been observed by Akebono. The IDB is identified as a sharp and deep dip at about 10 keV in ion spectra, which is usually observed at latitudes below the discrete auroral region over several degrees or more. As the ion motion of this energy in this inner part of the magnetosphere is basically described by the adiabatic theory, we have numerically traced the ion drift trajectories. From the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
38
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 17 publications
6
38
2
Order By: Relevance
“…Considering the relatively quiet magnetospheric activity level for this event, as well as the stationarity of the structure between the inbound and the out- bound leg of the Cluster orbit and the typical energy range of the observed nose structure (i.e. 6.45 keV in average), this feature seems to be related to the stationary nose structures described in previous papers (Shirai et al, 1997). The nose structure is also seen in the O + spectrogram.…”
Section: February 2002mentioning
confidence: 60%
See 4 more Smart Citations
“…Considering the relatively quiet magnetospheric activity level for this event, as well as the stationarity of the structure between the inbound and the out- bound leg of the Cluster orbit and the typical energy range of the observed nose structure (i.e. 6.45 keV in average), this feature seems to be related to the stationary nose structures described in previous papers (Shirai et al, 1997). The nose structure is also seen in the O + spectrogram.…”
Section: February 2002mentioning
confidence: 60%
“…Moreover, these structures (that will be referred in the following as "stationary nose structures") appear regardless of the magnetospheric activity level. Using an ion drift trajectory model, Shirai et al (1997) were able to reproduce such structures, and showed that they are the consequence of the open/close character of the particle orbits: at the Akebono location, corotation electric field is sufficient to close the orbit (around the Earth) of low energy particles which are drifting eastward. Also, the magnetic field gradient is strong enough to close the orbits of high energy particles which are drifting westward.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations